A SURVEY ON SEVERAL POTENTIALLY PROBLEMATIC AREAS OF PRONUNCIATION FOR IRANIAN EFL LEARNERS - Amir Toghyani Khorasgani; Ali Toghyani Khorasgani; Narges Keshti Aray (University of Kuningan, 2015)
Almost all English language teachers get students to study grammar, vocabulary, etc., but some of these same teachers make little attempt to teach pronunciation in any overt way and only give attention to it in passing. Pronunciation teaching not only makes students aware of different sounds and sound features, but can also improve their speaking. Concentrating on sounds, making aware of where words should be stressed, where words made in mouth, give students information about spoken English and help them achieve the goal of improved comprehension and intelligibility. Pronunciation forms a natural link to other aspects of language use, such as listening, vocabulary, and grammar; ways of highlighting this interdependence in teaching need to be explored. The present paper looks at the problems which Iranian learners are deal with through learning English according to the differences between their segmental and suprasegmental patterns in phonology. Comparing the Persian vowel system with that of English reveals some significant differences in the following three areas: 1) the number of vowels, 2) tense/lax distinctions, and 3) the pure/glide. There are also noticeable differences in consonantal distributions between Persian and English such as their numbers, clusters, manner and place of articulation. The syllabus types of English and Persian are also cause a lot of problem in spoken language. The differences between word stress patterns in Persian and English also make problematic areas for Iranian students. In this paper, through detailed examination of Persian and English sound systems, some of the specific problems areas have been identified, especially in reference to some of the characteristic phonological differences between the two languages.Keywords: vowel, consonant, syllable type, stress pattern